Graphical Approach for RF Amplifier Specification in Radio over Fiber System: Maximum Power Issues - Teguh Prakoso; Munawar Agus Riyadi; Razali Ngah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Radio-over-fiber (RoF) technologies address wireless communication’s need for high data rate, protocol- transparency, and flexibility. One of challenge in RoF access point design is RF amplifier requirement that match to microwave-photonic link chosen and service range needed. This paper proposes a graphical approach as systematic method to solve the challenge. The method identifies two regions, i.e. (a) scalable region where amplifiers’ output 1-dB compression point (OP1dB) improvement can enhance system’s maximum input and output power, and (b) saturation region where any improvement on amplifiers’ OP1dB cannot improve AP’s maximum input and output power. The methods have been verified by system simulations. The errors at scalable and saturation regions are less than 1 dB and the standard deviation is no more than 0.6 dB. The error values around the breakpoint between scalable and saturation regions are around 1 dB. Therefore, the proposed graphical approach can be used in the specification tradeoff between RoF access point input and output power, amplifier’s gain and OP1dB.